Resilient Architectural Practices for Sustainable Urban Residences Futures to Achieve - Solomon Oisasoje Ayo-Odifiri & Andrew Ebekozien (SureBuilt Series, 2026)
Many cities in emerging economies are facing significant climate-related vulnerabilities, including rising temperatures, flooding, urban heat islands, erosion, and high carbon footprints. In developing nations like Nigeria, where these massive crises are predicted and experienced, their impacts render existing residential neighbourhoods vulnerable and uninhabitable, thereby posing a threat to Agenda 2063 if not addressed urgently. Innovative practices may not only reduce environmental and spatial impacts but also improve infrastructure resilience. This study explores resilient architectural practices (RAPs) for sustainable urban residence futures (SURF) in Nigeria, to achieve Agenda 2063 Aspirations. RAPs entail a passive climate design approach that includes adaptive façades, reflective building materials, solar shading devices, and daylight benefits. Others comprise optimising natural ventilation, extended roof eaves, deep verandas, optimal building orientation, and nature-based solutions. The researchers adopted a phenomenological qualitative research approach. Data collected via online open-ended questions administered to 40 architects, purposively selected from 3 major Nigerian cities, attained saturation with the 32nd participant. The elicited data were analysed and discussed in two themes. The findings showed passive, inclusive design principles, adoption of vernacular architectural style, climate-adaptive materials (CAM), and responsive management were RAPs for SURF. The study highlighted an iterative design process, robust policies linked to Agenda 2063 and the political will to enforce construction and environmental standards. Prioritising passive design and adopting elements of Nigerian traditional architecture in the construction of modern homes and the retrofitting of existing ones were emphasised. Integrating climate-responsive practices into academic curricula, licensure requirements, benchmarking housing plans, and partnering with built environment experts were advocated to advance Agenda 2063 for Nigeria's urban residences future. Organic